Surgeon involvement in clinical coding to improve data accuracy and remuneration in a shoulder and elbow unit. (February 2022) - Kyriacou, Steven; Butt, David; Rudge, Will; Higgs, Deborah; Falworth, Mark; Majed, Addie
Background: Clinical coders are dependent on clear data regarding diagnoses and procedures to generate an accurate representation of clinical activity and ensure appropriate remuneration is received. The accuracy of this process may potentially be improved by collaboration with the surgical team. Methods: Between November 2017 and November 2019, 19 meetings took place between the Senior Clinical Fellow of our tertiary Shoulder & Elbow Unit and the coding validation lead of our Trust. At each meeting, the Clinical Fellow assessed the operative note of cases in which uncertainty existed as to the most suitable clinical codes to apply and selected the codes which most accurately represented the operative intervention performed. Results: Over a 24-month period, clinical coding was reviewed in 153 cases (range 3–14 per meeting, mean 8). Following review, the clinical coding was amended in 102 (67%) of these cases. A total of £115, 160 additional income was generated as a result of this process (range £1677–£15, 796 per meeting, mean £6061). Only 6 out of 28 (21%) cases initially coded as arthroscopic sub-acromial decompressions were correctly coded as such. Discussion: Surgeon input into clinical coding greatly improves data quality and increases remuneration received for operative interventions performed.